Virtual Visits: Managing prenatal care with modern technology. Issue 1 (January 2016) - Pflugeisen, Bethann M.; McCarren, Christi; Poore, Stephen; Carlile, Malinda; Schroeder, Richard
Abstract: Purpose: To implement and evaluate a novel model of prenatal care for low-risk pregnant women that intersperses in-person physician visits with nurse practitioner visits conducted via videoconference. Methods: This Quality Improvement initiative gave low-risk pregnant women the option of enrolling in a Traditional ( N = 941) or Virtual Visit ( N = 117) track for their prenatal care. Traditional patients had 14 physician visits and a postpartum visit. Virtual Visit patients had nine physician visits, five prenatal videoconference visits, and a 2-week postpartum videoconference visit. Measured outcomes include demographic variables, pregnancy and birth outcomes, and use of the health system. Logistic regression was used to assess demographic factors affecting track enrollment decisions. Multivariate logistic regression and ANCOVA methods were used to evaluate pregnancy and birth outcomes, adjusting for relevant confounding variables. Results: Women enrolling in the Virtual Visit track were twice as likely to be partnered ( p = 0.03) and not enrolled in government supplemental nutrition assistance ( p = 0.01). They were seven times as likely to have been pregnant at least once before this enrollment ( p < 0.001). Although a significantly higher percentage of Virtual Visit patients had a preeclampsia diagnosis ( p = 0.02, N = 10 Virtual Visit patients), no other differences were observed between the groups in pregnancy/birth outcomes or health system use. Clinical Implications: The Virtual Visit program provides low-risk pregnant women with a new model of prenatal care that does not appear to demonstrate increased risk for mother or baby compared to a traditional model. This program may be especially appealing to middle-/high-income mothers who are partnered and already have children. Abstract : Virtual prenatal visits interspersed with in-office visits are a novel way to meet the needs of healthy low-risk pregnant women and may offer the ability to improve efficiency while decreasing costs.